Similarity search and applications : 10th International Conference, SISAP 2017, Munich, Germany, October 4-6, 2017, Proceedings - Beecks, Christian ; Borutta, Felix ; Kröger, Peer ; Seidl, Thomas (Springer, 2020)
This book constitutes the refereed proceedings of the 10th International Conference on Similarity Search and Applications, SISAP 2017, held in Munich, Germany, in October 2017. The 23 full papers presented were carefully reviewed and selected from 53 submissions. The papers deal with issues surrounding the theory, design, analysis, practice, and application of content-based and feature-based similarity search. They are organized in the following topical sections: approximate similarity search; improving similarity search methods and applications; distances for complex objects; outlier detection; indexing and applications; and applications and specific domains.